Mother’s Knowledge regarding the Functions of Children's Primary Teeth in Salapian District, Langkat-North Sumatera - Essie Octiara; Grace Anastasia Tarigan (TALENTA, 2022)
Primary teeth play a role in mastication, speech function, appearance, and as a provider of space for children's permanent teeth. Mothers need to know the functions of their children's primary teeth so they are willing to take care of their children's teeth. This study aims to see the relationship of a mother’s knowledge regarding the functions of children’s primary teeth to the number of children and the level of education in Salapian District, Langkat. This study is an analytical study with a cross-sectional design. The research subjects were 100 people; 30 prospective mothers, 30 mothers with one child, and 40 mothers with more than one child. Data were collected using the interview technique and the analytical test used was the Kruskal Wallis test with a significance value of p<0.05. The results showed that 15 respondents (15%) had a good level of mother’s knowledge regarding the functions of children’s primary teeth, 36 respondents (36%) were in an insufficient category, and 49 respondents (49%) were in less category. Statistical analysis showed a significant relationship between the mother’s knowledge regarding children’s primary teeth functions the number of children and education level (p=0.001 and p=0.001). This study concluded that mothers who have many children have a better knowledge about functions of primary teeth than mothers with few children. Mothers with higher education levels have a better level of knowledge than mothers with primarysecondary education. Keywords: mother’s knowledge, functions of primary teeth, education level, number of children